EFFECT OF TRANSPLANTING METHODS, NP- FERTILIZER RATES ON LEAF LENGTH OF FEMALE DATE PALM (PHOENIX DACTYLIFERA L.) OFFSHOOT - Isyaku, M. S.; Yakubu, Haruna; Muhammad, A. M.; Hamza, A. M.; Zamfara, M. I. (FUDMA JOURNAL OF SCIENCES, 2020)
ABSTRACTStudies on the effect of transplanting methods and NP â€“ fertilizer rates on leaf length of a female date palm offshoot have been conducted over a period of 25 months (September, 2017 â€“ September 2019). The trial was sited at the Date Palm Research Sub â€“ station/ Federal University Dutse (11o50â€™N, 09o25â€™E) in the Sudan Savanna ecological zone of Nigeria.  The treatments consisted of two transplanting methods (Direct: detachment of offshoot from the parent palm and directly transplanting into the field, and Indirect: detachment of offshoot from the parent palm and keeping in the nursery for 3 months before transplanting into the field) and five NP fertilizer rates Control (0g N + 0g P), 80g N + 40g P, 160g N + 80g P, 240g N +120g P and 320g N + 160g P) arranged in a randomized complete block design with three replications. Indirect transplanting of date palm through nursery proved more effective than direct transplanting as it produces statistically longer leaves which are an indication of better chances of crop survival, establishment and yield. Rate 320g N +160g P statistically outperformed other rates in the production of longer leaves throughout the sampling periods. Interaction between transplanting methods and fertilizer rates was highly significant in most of the sampled periods except in June and September, 2019. A combination of indirect transplanting method with rate 320g N +160g P that produced longer leaves is recommended for adoption  in the Sudan Savannah ecological zone of Nigeria.
Keywords: Date palm offshoot, direct transplanting method, indirect transplanting method NP- fertilizer and leaf length.